Des chiens pour protéger contre les loups des brebis en parcs clôturés : une pratique nouvelle et encore problématique - Baptiste Potet; Charles-Henri Moulin; Michel Meuret (Revue de Géographie Alpine)
Predation by wolves affects all livestock farming systems, including those having different batches of animals being simultaneously grazed in distinct and sometimes distant fenced pastures scattered over a landscape. In the absence of a responsible human herding and watching over his flock or herd, livestock protection by the sole combination of fences and guard dogs is a new practice in France, that has not yet received much attention in public policy recommendations. We used several sources of knowledge, from the scientific literature to experiences of breeders interviewed in the Southern Alps, to analyse three issues to improve the effectiveness of the practice: the number of guard dogs required per batch of animals, the complementarity of dogs within their working group, and the land area to be protected by dogs. In each case, several dogs are necessary. Within their group, the guard dogs can play complementary roles and this optimizes protection. The rearrangement of dog groups during the year can cause difficulties. It may be appropriate sometimes to allow guard dogs to cross fences, so that they do not have to wait for wolves to jump or dig underneath. But in a densely populated and frequented country such as France, allowing protection by dogs on the periphery of fenced pastures faces a high risk of conflict with other land users. When grazing lands become risky areas for hikers or hunters confronted with guard dogs, the sustainability of outdoor livestock farming may be called into question.